MICROPHYSICAL AND DYNAMICAL CHARACTERISTICS OF HAIL-BEARING CONVECTIVE CLOUDS IN DEPOK: THE CASE OF 28 OCTOBER 2024 - Zikri, Muhammad Aulia; Alghazali, Muhammad Fathurrachman; Alamin, Mirza Virgiansah; Zakir, Achmad; Mulya, Aditya (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2026)
This study investigates the microphysical and dynamical characteristics of hail-producing convective clouds over the Depok region, Indonesia, through a case study of the event on 28 October 2024. A multi-data approach was applied by integrating weather radar data, Himawari-9 satellite, and ERA5 atmospheric reanalysis. Radar analysis revealed intense convective cores with reflectivity exceeding 55–60 dBZ, high Vertically Integrated Liquid (VIL) values (~50 mm), and ZHAIL probabilities above 80%, indicating well-developed hail cores. Satellite observations showed cloud growth and extremely low cloud-top temperatures coinciding with peak radar signatures. Although Convective Available Potential Energy (CAPE) values were relatively modest, reanalysis data indicated strong moisture availability, deep-layer instability, and favorable wind shear. These results demonstrate that hail formation in tropical urban regions is driven by the combined effects of moisture-rich environments, deep atmospheric instability, and organized convective dynamics rather than by high CAPE alone.